An annotated checklist and keys to the species of Copepoda Harpacticoida (Crustacea) - Wells, J. B.j. (Zootaxa, 2007)
A checklist of the approximately 4300 species of Copepoda Harpacticoida is presented. It is prepared according to the opinions of the latest revisers and adopts the phylogenetic system of Seifried (2003). The opportunity is taken to formally propose replacement names for preoccupied taxa (p. 14). Comments are provided on other taxonomic issues. A dichotomous key to families is followed by tabular keys to species within each family.